Perkawinan Sasuku di Nagari Talang Babungo Tahun 2008-2019 - Asmaul Husna; Rusdi Rusdi (PAMA Aksara, 2023)
This study aims to describe and explain the prohibition of ethnic marriage in Nagari Talang Babungo, Hiliran Gumanti District, Solok Regency. Sasuku marriage is something that is strictly prohibited in the marriage custom of Nagari Talang Babungo. Sasuku marriage is a barrier for people who will marry with the same tribe. Nevertheless, the marriage of the Sasuku in the Talang Babungo village still occurs. This research uses descriptive qualitative research method. Data were collected by interview, observation and documentation. From the results of the research that has been done, it can be seen that ethnic marriages in Nagari Talang Babungo in 2008-2019 have been carried out by the community. There were 4 couples who had ethnic marriages in Nagari Talang Babungo from 2008-2019. This is because of the change in customary sanctions for people who are currently engaged in sasuku marriages. This change in customary sanctions can be seen from the sanctions given to couples who carry out sasuku marriages in Nagari Talang Babungo in 2008 until now.